2008
DOI: 10.1016/j.jmaa.2007.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Geometric mean and triangles inscribed in a semicircle in Banach spaces

Abstract: We consider the triangles with vertices x, −x and y where x, y are points on the unit sphere of a normed space. Using the geometric means of the variable lengths of the sides of these triangles, we define two geometric constants for Banach spaces. These constants are closely related to the modulus of convexity of the space under consideration, and they seem to represent a useful tool to estimate the exact values of the James and Jordan-von Neumann constants of some Banach spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…for a real number p, by considering Hölder's means. It is obvious that A 2 (X) = H 1 (X) (see [3]) and T(X) = H 0 (X) (see [1]), that is,…”
Section: Definition 23 ([11])mentioning
confidence: 99%
See 2 more Smart Citations
“…for a real number p, by considering Hölder's means. It is obvious that A 2 (X) = H 1 (X) (see [3]) and T(X) = H 0 (X) (see [1]), that is,…”
Section: Definition 23 ([11])mentioning
confidence: 99%
“…The constant A 2 (X) was defined by Baronti, Casini and Papini in [3] by considering the arithmetic mean of x + y and x − y and the constant T(X) was introduced by Alonso and Llorens-Fuster in [1] by considering the geometric mean between x + y and x − y . It is noteworthy that X is uniformly non-square if and only if H p (X) < 2 (see [8]).…”
Section: Definition 23 ([11])mentioning
confidence: 99%
See 1 more Smart Citation
“…Let X be the 2 − 1 space. It has been shown that for this space A 2 (X) = 1 + 1/ √ 2 (see [1,Example 25]) and J (X) = √ 8/3 (see [10,Example 2]). Thus…”
Section: Llorens-fuster [1 Theorem 26] Asmentioning
confidence: 99%
“…Therefore, J(X ) = J X ,−∞ (1). It is obvious that the James type constants include some known constants, such as Alonso-Llorens-Fuster's constant T (X) [4], Baronti-Casini-Papini's constant A 2 (X) [5], Gao's constant E(X ) [6] and Yang-Wang's modulus γ X (t) [7]. These constants are defined by T (X) = J X ,0 (1), A 2 (X) = J X ,1 (1), E(X ) = 2J 2 X ,2 (1) and γ X (t) = J 2 X ,2 (t).…”
Section: Introductionmentioning
confidence: 99%